2020
DOI: 10.3389/fonc.2020.591799
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and Allied Health Research Priorities in the Care of Patients With Thoracic Malignancies: An International Cross-Sectional Survey

Abstract: Background: There is currently no evidence of research priorities from nurses and allied health professionals working in the field of thoracic malignancies, which could provide strategic directions for funders, policy makers, and researchers. Objective: The aim of this study is to identify the priorities for lung cancer and other thoracic malignancies research and practice in nurses and allied health professionals. Methods: Descriptive cross-sectional web-based international survey conducted through internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In another study, seven themes emerged; health promotion, National Health Service processes, new tests, population characteristics, screening (including risk stratification), symptom awareness, and symptom investigation. 22 Moreover, Molassiotis and Fraser 23 reported that key priority categories in cancer research were related to the development and evaluation of new interventions; symptom management interventions; healthcare system issues; treatment-related research (immunotherapy; targeted therapies); persistent/late effects management (fatigue; pulmonary toxicity); risk reduction, and screening research. The specific topic with the highest endorsement was the development of interventions to improve quality of life.…”
Section: Priorities For Oncology Researchmentioning
confidence: 99%
“…In another study, seven themes emerged; health promotion, National Health Service processes, new tests, population characteristics, screening (including risk stratification), symptom awareness, and symptom investigation. 22 Moreover, Molassiotis and Fraser 23 reported that key priority categories in cancer research were related to the development and evaluation of new interventions; symptom management interventions; healthcare system issues; treatment-related research (immunotherapy; targeted therapies); persistent/late effects management (fatigue; pulmonary toxicity); risk reduction, and screening research. The specific topic with the highest endorsement was the development of interventions to improve quality of life.…”
Section: Priorities For Oncology Researchmentioning
confidence: 99%
“…In the elderly, insomnia is the most significant sleep disorder and its natural reduction in sleep duration can generate anxiety and worsen insomnia symptoms (Patel et al, 2018;Gulia & Kumar, 2018). Therefore, the participation of the multidisciplinary team in the evaluation process is essential (Molassiotis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%